Anatomy and Histochemistry of Seed Coat Development of Wild (Pisum sativum subsp. elatius (M. Bieb.) Asch. et Graebn. and Domesticated Pea (Pisum sativum subsp. sativum L.) - Zablatzká, Lenka; Balarynová, Jana; Klčová, Barbora; Kopecký, Pavel; Smýkal, Petr (International journal of molecular sciences, 2021)
In angiosperms, the mature seed consists of embryo, endosperm, and a maternal plant-derived seed coat (SC). The SC plays a role in seed filling, protects the embryo, mediates dormancy and germination, and facilitates the dispersal of seeds. SC properties have been modified during the domestication process, resulting in the removal of dormancy, mediated by SC impermeability. This study compares the SC anatomy and histochemistry of two wild (JI64 and JI1794) and two domesticated (cv. Cameor and JI92) pea genotypes. Histochemical staining of five developmental stages: 13, 21, 27, 30 days after anthesis (DAA), and mature dry seeds revealed clear differences between both pea types. SC thickness is established early in the development (13 DAA) and is primarily governed by macrosclereid cells. Polyanionic staining by Ruthenium Red indicated non homogeneity of the SC, with a strong signal in the hilum, the micropyle, and the upper parts of the macrosclereids. High peroxidase activity was detected in both wild and cultivated genotypes and increased over the development peaking prior to desiccation. The detailed knowledge of SC anatomy is important for any molecular or biochemical studies, including gene expression and proteomic analysis, especially when comparing different genotypes and treatments. Analysis is useful for other crop-to-wild-progenitor comparisons of economically important legume crops.
Keywords: macrosclereids; hrách setý; permeability; Genotype; Germination; domestikace; Seeds; testa; Pisum sativum; Endosperm; semena rostlinná; seed coat; pea; Domestication; proteomika; dormancy; genotyp; Proteomics; endosperm; domestication; Magnoliopsida; legumes; klíčení